2021
DOI: 10.3892/ijmm.2021.4852
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aerobic glycolysis alleviates sepsis‑induced acute kidney injury by promoting lactate/Sirtuin 3/AMPK‑regulated autophagy

Abstract: Metabolism reprogramming influences the severity of organ dysfunction, progression to fibrosis, and development of disease in acute kidney injury (AKI). Previously we showed that inhibition of aerobic glycolysis improved survival rates and protected septic mice from kidney injury. However, the underlying mechanisms remain unclear. In the present study, it was revealed that sepsis or lipopolysaccharide (LPS) enhanced aerobic glycolysis as evidenced by increased lactate production and upregulated mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…Morigi et al [ 94 ] suggested a similar protection with activation of Sirtuin 3 in a model of nephrotoxic AKI. Protection from AMPK activation in our CLP model was associated with an increased expression in Sirtuin 3 [ 64 ], supporting the findings by Tan et al [ 93 ] and Morigi et al [ 94 ]. These data are consistent to demonstrate that, regardless of the specific molecular mechanism, activation of AMPK during sepsis protects against AKI and decreases mortality.…”
Section: Metabolic Reprogramming: a Therapeutic Target Invoking Tolerancesupporting
confidence: 90%
See 1 more Smart Citation
“…Morigi et al [ 94 ] suggested a similar protection with activation of Sirtuin 3 in a model of nephrotoxic AKI. Protection from AMPK activation in our CLP model was associated with an increased expression in Sirtuin 3 [ 64 ], supporting the findings by Tan et al [ 93 ] and Morigi et al [ 94 ]. These data are consistent to demonstrate that, regardless of the specific molecular mechanism, activation of AMPK during sepsis protects against AKI and decreases mortality.…”
Section: Metabolic Reprogramming: a Therapeutic Target Invoking Tolerancesupporting
confidence: 90%
“…Sirtuin 3 has been proven to protect from AKI by improving the mitochondrial fusion and respiration [ 92 ]. Tan et al [ 93 ] revealed that the aerobic glycolysis inhibitor 2-DG increased autophagy via the Sirtuin 3/AMPK pathway in CLP-induced sepsis mice resulting in protection against sepsis-associated AKI. Morigi et al [ 94 ] suggested a similar protection with activation of Sirtuin 3 in a model of nephrotoxic AKI.…”
Section: Metabolic Reprogramming: a Therapeutic Target Invoking Tolerancementioning
confidence: 99%
“…In addition to energy production, aerobic glycolysis and the resulting metabolites are also involved in the regulation of various pathophysiology processes such as cell proliferation, extracellular matrix production, autophagy, and apoptosis ( 46 ). Although there is only a limited number of studies on the relationship of the Warburg effect and AKI ( 47 ), recent studies have provided compelling evidence that the Warburg effect contributes to the progression of kidney diseases such as polycystic kidney disease (PKD) and diabetic kidney disease (DKD) ( 38 , 48 , 49 ). Rowe et al observed that aerobic glycolysis was a preferred source of energy rather than oxidative phosphorylation in Pkd1 −/− mouse embryonic fibroblasts.…”
Section: Regulation Of Glucose Metabolism In Kidney Diseasesmentioning
confidence: 99%
“…Although this pathway is less efficient in producing ATP compared to OXPHOS, it allows the fast generation of biosynthetic precursors necessary for immune cell proliferation. This switch to aerobic glycolysis has been reported under inflammatory conditions such as sepsis and lipopolysaccharide (LPS) stimulation, as well as in some autoimmune diseases such as rheumatoid arthritis [20,21]. Beyond its role in supporting cell proliferation, immune cell metabolism actively regulates the differentiation, polarization and activation of several immune cell types such as T cells and macrophages, as summarized in the next sections.…”
Section: Sirtuins Translate Metabolic Cues To Immune Responsesmentioning
confidence: 85%